Negosiasi Kekuasaan di Pantai Lasiana: (Studi atas Tiga Model Pengelolaan Lahan (Pemerintah, Tokoh Lokal, dan Swasta)) - Milsa M. I. Hanas; Ananias R. P. Jacob; Diana S. A. N. Tabun (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze power negotiation among the government, local figures, and private actors in land management within the Lasiana Beach Tourism Area, Kupang City, using a qualitative case study approach. Data were collected through in-depth interviews, field observations, and documentation involving informants from local government, site managers, local leaders, private sector actors, and MSME participants. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, and was guided by John Gaventa’s Power Cube theory, which consists of dimensions of forms of power, spaces of power, and levels of power. The findings show that land management in Lasiana Beach results from complex and multipolar power negotiations among three actors. The government holds formal authority through regulations and policies but is not fully dominant due to hidden and invisible power exercised by local figures and private actors. Local figures rely on social and historical legitimacy to maintain influence, while private actors use capital strength and licensing access to strengthen their position. Power spaces include closed, invited, and claimed spaces that serve as arenas of negotiation. At the level dimension, local dynamics strongly affect policy implementation. Interactions among actors occur mainly through compromise, tolerance, and interest adjustment rather than open conflict. The study concludes that Lasiana Beach management is shaped not only by formal policy but also by social relations, informal practices, and strategic actor negotiations in coastal tourism governance.